From Rice to Oil Palm: the Historical Evolution of Peatland Reclamation in the Berbak Delta, Indonesia - Widjaja, Hermanu; Suwardi; Darmawan (JOURNAL OF TROPICAL SOILS, 2025)
The Berbak Delta in Jambi Province, Indonesia, underwent large-scale peatland reclamation in the 1970s as part of a transmigration program to develop rice fields. Initially, rice production averaged 3–4 tons/ha but declined to less than 1 Mg ha-1 due to the conversion of peat soils into acid sulfate soils. This decline was attributed to soil acidification from pyrite oxidation, which lowered soil pH. Currently, rice cultivation persists in areas near rivers influenced by tidal brackish water. In response to declining yields, a technological package for acid sulfate soil management was introduced, including canal water management, pH improvement, and fertilizer application. It increased rice yields to over 5 Mg ha-1 in a 100-ha pilot project in 2005. However, by 2008, farmers began shifting to oil palm plantations due to higher income potential. This study examines land-use change from rice fields to oil palm plantations and its impact on the livelihoods of communities in the Berbak Delta. Land cover change analysis from 2013 to 2023 revealed a decrease in rice fields from 58.30% to 25.79% and an increase in oil palm plantations from 15.37% to 55.70%. Oil palm cultivation has demonstrated sustainability on reclaimed acid sulfate soils, leading to economic prosperity through improved infrastructure and housing, as well as increased private vehicle ownership.